Pelatihan Pembuatan Lubang Resapan Biopori untuk Pengolahan Sampah Rumah Tangga Menjadi Pupuk Kompos di Desa Beseran - Sholihul Abidin; Dhafa Satrio Rizki Wicaksana; Ria Fitrasih (Universitas Negeri Semarang, 2026)
Beseran Village faces challenges in managing household waste which has a negative impact on the environment. As a solution to overcome this problem, training in making biopore absorption holes was initiated to reduce the volume of waste while producing compost. The aim of this activity is to provide understanding and skills to village residents in utilizing organic waste through biopori technology. The objects of this activity are the residents of Beseran Village, especially PKK cadres and housewives. The methods used in this activity include socialization, direct demonstrations, and assistance in the practice of making biopore holes and processing organic waste into compost. The results of the activity show an increase in residents' knowledge and skills in processing household waste, as well as success in reducing the volume of waste and producing quality compost fertilizer. It is hoped that this training can become a model for sustainable waste management at the village level, as well as contribute to improving the environmental and economic quality of Beseran Village residents.